Implementing Holistic Education through Annual Activities to Foster the Character of Female Students at Darussalam Gontor Putri 8 Modern Islamic Boarding School - Hidayah, Afifah Nor; Jaenullah, Jaenullah; Izzah, Nailul (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study explores the implementation of holistic education through annual activities in shaping the character of female students at Darussalam Gontor Putri 8 Modern Islamic Boarding School. Holistic education at Gontor is not limited to classroom instruction but is also embedded in various extracurricular and institutional traditions such as Khutbatu-l-‘Arsy Introduction Week (PKA), Porseni, Panggung Gembira, and scouting activities. These activities serve not merely as formal events, but as systematic platforms for internalizing core character values including discipline, responsibility, leadership, cooperation, and independence. Employing a descriptive qualitative approach, this research collected data through observations, in-depth interviews, and document analysis, with participants comprising fifth- and sixth-grade female students, supervising teachers, and archival records of annual activities. The findings reveal that students’ active involvement in planning and organizing these activities fosters comprehensive character development. They acquire leadership experience, decision-making ability, conflict resolution skills, teamwork, and accountability across diverse roles. Moreover, the activities nurture honesty, managerial competence, and solidarity within the student body. In conclusion, annual activities at Gontor function as a vital mechanism in implementing holistic education, effectively cultivating sustainable character values among female students. This study contributes to the discourse on character education by demonstrating how structured extracurricular traditions within Islamic boarding schools can serve as integral instruments of holistic education. It provides practical insights for educators and policymakers seeking sustainable models of character formation that extend beyond classroom learning, thereby reinforcing the role of institutional culture in shaping students’ moral and social competencies